Analisis minat kunjung ulang di Café Kopi Kappie Pucang Adi Surabaya - Pratama, Rafliansyah; Purwanto, Sugeng (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Progress in the business world in today's modern era has undergone significant changes and improvements. So, with the high interest of coffee lovers in Surabaya, there are many cafes in Surabaya. Each coffee café always offers different concepts and tastes, thus making the competition for several coffee cafes in Surabaya more competitive. The various prices offered by each coffee shop make marketing influencers of the interest of consumers to visit again. This study aims to determine the effect of price perception and experiential marketing on revisit interest at the Kappie Coffee Café in Pucang Adi Surabaya. methods of data collection using the Survey Method. The research method used is quantitative research methods using data analysis techniques using SmartPLS as an analytical tool. The results of this study note that price perception and experiential marketing have a significant effect on revisit interest. The more appropriate the experiential marketing provided by the Kappie Pucang Adi Surabaya coffee cafe, the higher the interest in repeat visits, and the Kappie Pucang coffee cafe maintains the quality that it already has and always maintains and chooses the best raw materials to make products that will be given to customers visitors.